The land system as a platform for integration and interpretation of complex environmental-society relations (Sustainability in Debate, 2017)
The Land System, as a terrestrial component of the Earth System, constitutes an eminently coupled environment-societies system. For operating in complex interface between social and natural fields, the land system science emerges as a platform for integration of different dimensions of environmental change. In this sense, the present paper aims to explore relations between this theme, interdisciplinarity and complexity. The paper identifies this integration bias from three characteristics: a) the potential for representation of plurality and multidimensionality of several knowledge systems, in different stages of stabilization; b) be endowed of a role of mediation in socioecological processes, acting as cause and consequence, simultaneously; and c) as a result of previous items, be framed as an eminently complex system and, thus, face up to its set of characteristics and behaviors.